Intensity of Misconception in Software Engineering - Inuwa, Muhammad Muhammad; Varol, Asaf (Institute of Electrical and Electronics Engineers Inc., 2019)
"Misunderstanding is generally simpler than true understanding, and hence has more potential for popularity."-Raheel Farooq. Misconception can be a great distortion to someone's carrier. The misconception of believing that software engineers can troubleshoot personal computing problems motivated the implementation of the research. The research is aimed at finding out the severity of misconception in Software Engineering field. Fifty-one voluntary software engineering students from year 1, 2 and 3 participated in the research. The data were fetched using questionnaire and analyzed using SPSS statistical application. The misconceptions were analyzed in the discussion section to dissect and compare it with the real view from the scholars. The result concluded that the participants hold a great misconception about their field of study. However, the severity of the misconception feared that it might cause a negative effect to the software development industries which is related to the cost and the quality of the software production. This article can be a contribution to those pursuing their carrier in Software Engineering to understand what is actually needed from them. © 2019 IEEE.
1st International Informatics and Software Engineering Conference, IISEC 2019 -- 6 November 2019 through 7 November 2019 -- Ankara -- 157111
Keywords: Misconception; Software Engineering; SPSS